Healthy lifestyles in times of Covid-19 - Adys Castro Barberena; Vania E. Santiesteban Vázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Health risks have increased today, industrialization, urbanization, globalization and epidemics have led to changes in the lifestyles of individuals that have affected their socioeconomic conditions and cultural habits. There are multiple diseases in which it is very important to maintain healthy lifestyles nowadays, to favor their control. Among them, high blood pressure stands out. This work aims to address some guidelines and points of view about how healthy lifestyles are managed for the control of chronic non-communicable diseases in times of the COVID-19 pandemic, from Primary Health Care.